Perancangan Sistem Informasi Perpustakaan SD Negeri 2 Sumberwaru - Afandi, Irfan; Abd. Ghofur (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2025)
In the field of education, libraries serve as a vital medium supporting every teaching and learning activity. This is because libraries provide almost all the knowledge and information needed by educators to find references for their teaching materials, and by students to find resources to complete assignments or simply to read books. However, not all schools with libraries have a library information system that supports all activities within the library; many still rely on manual management methods. Therefore, an effective and efficient library information system is needed for library management, and this system must be tailored to the needs and conditions of SD Negeri 2 Sumberwaru.